A new approach to biomechanical analysis in cycling to introduce science to future data acquisition - Imbery, F.; Schoberer, U.; Leo, P. (Journal of Science and Cycling, 2021)
With the invention of power measurement systems for cyclists by Ulrich Schoberer in 1986, the training of riders and their equipment has been put to another level. Over time, more and more parameters for the assessment of physiological processes and biomechanical analysis have been established1), 2), 3). Biomechanical factors play a more important role in defining new indicators to search for the smallest detail and advantage4), 5), 6). The aim of this single case study is to show the improved power measurement and a possible significant research benefit that will come up in the future using a new development of SRM. It will be demonstrated by evaluating a ride on an Indoortrainer with an oval and round chainring and two rides of different training targets. The amount of the highly resolved recorded data has improved with the Powermeter prototype what may also lead to many exciting discussions and approaches to introduce or rethink parameters.